Implementation of Legal Protection of Photographic Works Based on Article 40 Paragraph (1) Letter K of Act Number 28 of 2014 Concerning Copyrights - Dewi Narakarti; Mahfud Fahrazi; Dwi Sisbiantoro (UNISKA LAW REVIEW, 2023)
Legal protection for photographic works has been regulated in Act Number 28 of 2014 concerning Copyright. The more people who are connoisseurs and practitioners of photography, as well as the methods and patterns of publication in the field of photography, the more interesting it is to analyze how the law is applied in society. This study aims to analyze the application of legal protection to photographic works based on Article 40 paragraph (1) Letter K of Act Number 28 of 2014 concerning Copyright, as well as what efforts should be made by the government to provide protection for photographic works. This research was conducted by empirical method. The results of this study indicate that the implementation of legal protection for photographic works based on Article 40 paragraph (1) Letter K Act Number 28 of 2014 concerning Copyright is still lacking in its application, due to several factors that become obstacles. Many parties are actually aware of the existence of protection for photographic works, but many also underestimate the violations committed. This happened due to several factors, including firstly a lack of understanding of the protection of Photographic Copyrights. As well as the government should make more efforts to disseminate understanding about the importance of protecting copyrighted works of photography, because regional offices of the Directorate General of Intellectual Property Rights are only in big cities, it is necessary for Regency or City Governments to participate in carrying out preventive and repressive legal protection efforts.